The bracteate as economic idea and monetary instrument - Roger Svensson (Research Institute of Industrial Economics (IFN), 2013)
Although the leaf-thin bracteates are the most fragile coins in monetary history, they were the main coin type for almost two centuries in large parts of medieval Europe. The usefulness of the bracteates can be linked to the contemporary monetary taxation policy. Medieval coins were frequently withdrawn by the coin issuer and re-minted, where people had to pay an exchange fee. Bracteates had several favourable characteristics for such a policy: 1) Low production costs; and 2) various pictures could be displayed given their relatively large diameter, making it easy to distinguish between valid and invalid types. The fragility was not a big problem, since the bracteates would not circulate for a long period. When monetization increased and it became more difficult to handle re-coinage (around 1300), the bracteates lost their function as the principal coin. However, for a further two centuries (1300-1500) they were used as small change to larger denominations.
Keywords: E31; E42; E52; N13; 330; Bracteates; medieval coins; re-coinage; short-lived coinage system; monetization; monetary taxation policy; small change